Shipping canals on the downstream migration route of European eel (Anguilla anguilla): Opportunity or bottleneck?. Issue 1 (20th July 2020) - Vergeynst, Jenna; Pauwels, Ine; Baeyens, Raf; Mouton, Ans; De Mulder, Tom; Nopens, Ingmar
Abstract: Migrating fish species are worldwide in decline due to several global changes and threats. Among these causes are man‐made structures blocking their freshwater migration routes. Shipping canals with navigation locks play a dual role in this. These canals can serve as an important migration route, offering a short cut between freshwater and the sea. In contrast, the navigation locks may act as barriers to migration, causing delays and migration failures. To better understand these issues for downstream migrating fish, we studied the behaviour of European eels ( Anguilla anguilla ) in the Albert Canal at two scales. The mid‐scale contained a 27‐km canal pound confined by two navigation lock complexes, in which we released and tracked 86 silver eels. The small scale was a 200 × 150 m area just in front of the most downstream complex of the canal pound, where we analysed the behaviour of 33 eels in relation to the flow field resulting from a computational fluid dynamics (CFD) model. This paper discusses the factors influencing fish behaviour, and the relation between these behaviours on both scales. On the mid‐scale, migration efficiency resulted from a combination of intrinsic behaviour and flow in the canal pound. Also on the small scale, intrinsic behaviour influenced the success to pass the navigation lock. Increasing the flow would create more attraction and passage opportunities and hence facilitate migration through shipping canals, but only if this flow guides the fish through safe passage routes.